REFLECTION OF PROPERTY RELATIONS IN ECONOMIC CATEGORIES AND LAWS - A. I. Vankevich (Наука и техника)
Property is considered as a definite social form of material benefits appropriation, their advance in relations between people. Its essence is revealed by means of objective economic forms, industrial relations. In this connection the paper justifies a method for scientific knowledge of property while analyzing economic categories and laws because it is a subsystem of industrial relations system and it is realized in this system.